Herbicide Intoxication: Still A Threat in Developing Countries - Stevanus Eliansyah Handrawan; Mayang Indah Lestari; Zulkifli (Journal of Anesthesiology and Clinical Research, 2020)
The critically ill patient has severe respiratory, cardiovascular or neurological disorder often in combination. The critically ill patient needs intensive care unit (ICU) admission and strict monitoring. Intoxication commonly experienced in a critically ill patient in ICU and can complicate management. In developing countries, poisoning of herbicide still common and used for suicide attempts. Herbicides such as paraquat and glyphosate are often used because of their availability. Paraquat and glyphosate have high mortality rate primarily as a suicide attempt agent in developing countries. The primary target for paraquat toxicity is in the lung and can cause lung fibrosis. Severe glyphosate intoxication can cause dehydration, hypotension, pneumonitis, oliguria, loss of consciousness, liver dysfunction, acidosis, hyperkalemia and dysrhythmia. Diagnosis for herbicide intoxication needs a history of herbicide ingestion, physical examination and laboratory examination. Stabilisation and supportive therapy is the only choice, and there is still no specific treatment for herbicide intoxication. The intoxication of herbicide particular critically ill patient because there is still no such specific treatment for these.